The effect of pulmonary rehabilitation for post-acute sequelae of SARS-CoV-2 infection in patients: a systematic review and meta-analysis - Yue, Yinghua; Han, Xinyi; Chen, Qiming; Dai, Lirong; Ai, Qingjuan; Zhang, Zhigang; Ma, Fangli; Gao, Jing (Frontiers in Rehabilitation Sciences, 2025)
BackgroundPost-acute sequelae of SARS-CoV-2 infection (PASC), also known as long COVID, are characterized by persistent symptoms such as fatigue, dyspnea, and reduced functional capacity. Pulmonary rehabilitation (PR) is recommended for chronic respiratory conditions, but its effectiveness in PASC, particularly across different delivery modes, remains uncertain.ObjectiveTo assess the impact of PR, including telerehabilitation and in-person modalities, on physical function, dyspnea, pulmonary function, fatigue, and quality of life in patients with PASC.MethodsWe conducted a systematic search of PubMed, Embase, the Cochrane Library, and Web of Science from inception to March 25 for controlled clinical trials assessing the effects of PR in PASC patients. Two independent reviewers performed study selection and data extraction. The risk of bias was assessed using the Cochrane Risk of Bias Tool, and data were analyzed using Review Manager (RevMan) 5.4.1. Effect sizes were reported as mean differences (MD) or standardized mean differences (SMD) with 95% confidence intervals (CI).ResultsTen randomized controlled trials involving 673 participants were included. Most studies were judged to have a moderate risk of bias. Compared with usual care, PR significantly improved six-minute walk distance (MD: 76.85 meters; 95% CI: 57.35–96.36; p < 0.001), maximal inspiratory pressure (MD: 17.63 cmH₂O; 95% CI: 4.50–30.76; p = 0.009), fatigue (SMD: −1.15; 95% CI: −1.83 to −0.48; p < 0.001), and quality of life (SMD: 1.73; 95% CI: 0.56–2.91; p = 0.004). No statistically significant improvement was found for dyspnea (MD: −0.41; 95% CI: −1.51 to −0.68; p = 0.46). Subgroup analyses showed no significant differences between telerehabilitation and in-person PR across all outcomes, including exercise capacity (p = 0.84), dyspnea (p = 0.86), fatigue (p = 0.93), and quality of life (p = 0.44).ConclusionsPR improves physical and functional outcomes in patients with PASC. Telerehabilitation offers a clinically equivalent alternative to in-person PR, supporting its broader implementation.